Comparison of pain with bupivacaine and bupivacaine-sufentanil combination in women undergoing cesarean section with spinal anesthesia: A double-blind randomized clinical trial - Hasan Zabetian; Mohammad Rahmanian; Nahid Tadayon; Navid Kalani (Mashhad University of Medical Sciences, 2022)
Introduction: Today, spinal anesthesia is the method of choice for most cesarean sections. Postoperative pain control has always been one of the main concerns of anesthesiologists. Therefore, this study was performed aimed to compare the amount of pain with the use of bupivacaine and bupivacaine-sufentanil combination in women undergoing cesarean section with spinal anesthesia.Methods: This double-blind randomized clinical trial study was performed in 2021 on 30 patients undergoing elective cesarean section referred to Motahari Hospital in Jahrom. Patients were randomly divided into two groups of bupivacaine and bupivacaine-sufentanil. Patients' pain was assessed at 2, 6, 12 and 24 hours after surgery. Data were analyzed by SPSS software (version 21) and T-test, Mann-Whitney and Chi-square tests. P<0.05 was considered statistically significant.Results: The results of Mann-Whitney test showed that the mean pain in 2 hours after surgery was higher in the bupivacaine group than the bupivacaine + sufentanil group (P = 0.03). At other times, the mean pain was not significantly different between the bupivacaine + sufentanil and the bupivacaine groups (P >0.05). The most common postoperative complication in bupivacaine + sufentanil group was pruritus (53.3%).Conclusion: The use of spinal sufentanil with intrathecal bupivacaine in cesarean section reduces the pain in the first hours after cesarean section.